How does information affect the comovement between interest rates and exchange rates? - Marcelo Sánchez (European Central Bank (ECB), 2006)
This paper compares the link between exchange rates and interest rates under full information and two alternative asymmetric information approaches. It also distinguishes between cases of expansionary and contractionary depreciations. Full information results are not robust to the presence of informational frictions. For economies exhibiting expansionary or strongly contractionary depreciations, such frictions lead to two optimal deviations from full information outcomes: i) under asymmetric information with signal extraction, the realisation of a relatively less frequent shock leads the central bank to behave as if a more likely disturbance had instead taken place; and ii) under asymmetric information without signal extraction, the monetary authority does not react on impact to shocks. Finally, in the case of mildly contractionary depreciations, both asymmetric information models predict a lack of response of the central bank to aggregate demand shocks, as opposed to an offsetting movement in interest rates under full information.
Keywords: E52; E58; F31; F41; 330; Emerging market economies; exchange rate; imperfect information; monetary policy; transmission mechanism; Geldpolitische Transmission; Wechselkurs; Zins; Geldpolitik; Unvollkommene Information; Asymmetrische Information; Schwellenländer; Theorie